Skill-Biased Share-Altering Technical Change in Spatial General Equilibrium - Alberto Dalmazzo; Antonio Accetturo; Guido de Blasio (European Regional Science Association (ERSA), 2011)
The paper consider the skill-biased "share-altering" technical change hypothesis in a spatial general equilibrium model where skilled and unskilled individual may exhibit different preferences for local amenities. A main novelty - both for labour and urban economics- is that, under this hypothesis, skill-biased technical change can be readily represented by simple Cobb-Douglas production functions, rather than CES technologies. We then analyse the local labour markets equilibrium, where the adoption of new technologies may require an adequate proportion of skilled workers.
Keywords: O33; R12; R23; J31; 330; skill-biased technical change; share-altering technologies; local labour markets